The serial vision method in vernacular architecture research of the cultural heritage of Sveti Stefan - Koprivica, Goran (Arhitektura i urbanizam, 2026)
Formerly a medieval fortification and a fishing village, the island of Sveti Stefan in Montenegro has functioned as a luxury “town hotel” for the past seventy years. Although declared a cultural heritage of national importance in 1960, its long-term lease to a foreign tenant, modifications to the vernacular environment, insufficient institutional involvement, and recent management practices indicate improper treatment. This study offers a view of Sveti Stefan in which its cultural and historical values, integrated into a complex vernacular ambiance, outweigh its economic importance. Using the Serial Vision Method, the author documents the spatial condition of a chosen path through a sequence of images, emphasizing the vernacular character of the cultural habitat. The method is integrative (providing a historical overview that complements the freehand drawings), practical (highlighting the problems that threaten the island’s authenticity), educational (showing potential as a learning tool for architectural students), and economical (requiring only basic equipment and modest financial resources). Observation of the delineated path 1–1 revealed the most significant modifications of the vernacular environment in terms of excessive greening, insufficient maintenance, and general commercialization. The Serial Vision of Sveti Stefan serves as a reference for improving the current state of the cultural heritage, offering a temporary alternative to the island’s restricted access.
Keywords: spatial analysis; vernacular architecture of Sveti Stefan; cultural heritage; Serial Vision Method